Advance directives and power of attorney for health care in the oldest-old - results of the AgeQualiDe study. - Luck, T.; Rodriguez, F. S.; Wiese, B.; van der Leeden, C.; Heser, K.; Bickel, H.; In der Schmitten, J.; Koenig, H. H.; Weyerer, S.; Mamone, S.; Mallon, T.; Wagner, M.; et al. (BMC Geriatr, 2017)
BACKGROUND: Completion of advance directives (ADs) and power of attorney (POA) documents may protect a person's autonomy in future health care situations when the individual lacks decisional capacity. As such situations become naturally much more common in old age, we specifically aimed at providing information on (i) the frequency of ADs/POA in oldest-old individuals and (ii) factors associated with having completed ADs/POA. METHODS: We analyzed data of oldest-old primary care patients (85+ years; including community-dwelling and institutionalized individuals) within the German AgeQualiDe study. Patients were initially recruited via their general practitioners (GPs). We calculated frequencies of ADs and POA for health care with 95% confidence intervals (CI) and used multivariable logistic regression analysis to evaluate the association between having ADs and POA and participants' socio-demographic, cognitive, functional, and health-related characteristics. RESULTS: Among 868 GP patients participating in AgeQualiDe (response = 90.9%), n = 161 had dementia and n = 3 were too exhausted/ill to answer the questions. Out of the remaining 704 (81.1%) dementia-free patients (mean age = 88.7 years; SD = 3.0), 69.0% (95%-CI = 65.6-72.4) stated to having ADs and 64.6% (95%-CI = 61.1-68.2) to having a POA for health care. Individual characteristics did not explain much of the variability of the presence/absence of ADs and POA (regression models: Nagelkerke's R(2) = 0.034/0.051). The most frequently stated reasons for not having ADs were that the older adults trust their relatives or physicians to make the right decisions for them when necessary (stated by 59.4% and 44.8% of those without ADs). Among the older adults with ADs, the majority had received assistance in its preparation (79.0%), most frequently from their children/grandchildren (38.3%). Children/grandchildren were also the most frequently stated group of designated persons (76.7%) for those with a POA for health care. CONCLUSIONS: Our findings suggest a high dissemination of ADs and POA for health care in the oldest-old in Germany. Some adults without ADs/POA perhaps would have completed advance care documents, if they had had received more information and support. When planning programs to offer advanced care planning to the oldest old, it might be helpful to respond to these specific needs, and also to be sensitive to attitudinal differences in this target group.
Keywords: *Advance Directives/ethics/legislation & jurisprudence/psychology/statistics & numerical data; Aged, 80 and over; Decision Making; Family Relations/*psychology; Female; Germany; Humans; Male; *Mental Competency; Personal Autonomy; Physician-Patient Relations/*ethics